Putting ITIL® into Practice: DevOps for ITIL® Practitioners. - Pultorak, David (linkedin.com, 2018)
Learn how to apply DevOps concepts and ITIL® within an enterprise IT organization. Examine where DevOps and ITIL® intersect and how to adapt each in an enterprise setting.